2003
DOI: 10.1038/ni878
|View full text |Cite
|
Sign up to set email alerts
|

Thymopoiesis independent of common lymphoid progenitors

Abstract: Early T lineage progenitors (ETPs) in the thymus are thought to develop from common lymphoid progenitors (CLPs) in the bone marrow (BM). We compared thymic ETPs to BM CLPs in mice and found that they differed in several respects. Thymic ETPs were not interleukin 7 (IL-7)-responsive and generated B lineage progeny with delayed kinetics, whereas BM CLPs were IL-7-responsive and rapidly generated B cells. ETPs sustained production of T lineage progeny for longer periods of time than BM CLPs. Analysis of Ikaros-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
519
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(549 citation statements)
references
References 38 publications
25
519
3
2
Order By: Relevance
“…2; Allman et al 2003;Yoshida et al 2006). However, after lymphoid lineage potential is established in these progenitors, IKAROS is not required for further commitment into the T-cell or B-cell lineages (Fig.…”
Section: Lymphoid Lineage Commitment: An Ikaros Time Outmentioning
confidence: 99%
“…2; Allman et al 2003;Yoshida et al 2006). However, after lymphoid lineage potential is established in these progenitors, IKAROS is not required for further commitment into the T-cell or B-cell lineages (Fig.…”
Section: Lymphoid Lineage Commitment: An Ikaros Time Outmentioning
confidence: 99%
“…This model was supported by the prospective isolation of cell populations with CLP and CMP function from the murine BM. 1,2 Recent evidence, however, indicated that BM CLPs are not physiological T-cell progenitors, as early thymic progenitors (ETPs) do not have the CLP phenotype 3 and CLPs are not present in the peripheral blood. 4 Instead, the thymus is most likely seeded by a multipotent progenitor.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest lymphocyte progenitor (ELP; Igarashi et al 2002) and later common lymphoid progenitor (CLP; Allman et al 2003) already initiate D H -J H rearrangements, which are completed during development to the early pro-B-cell stage (fraction B; Li et al 1993). As the ELP and CLP also give rise to T, NK, and dendritic cells (Kondo et al 1997;Traver et al 2000;Igarashi et al 2002), it may not be surprising that these cell types carry D H -J H -rearranged IgH alleles at low frequency (Kurosawa et al 1981;Born et al 1988;Corcoran et al 2003).…”
mentioning
confidence: 99%